PENGARUH MEDIA SOSIAL TERHADAP TINGKAT KETERAMPILAN KOMUNIKASI PADA REMAJA - Nur Suci Romadhona; Devi Putri Larasati; M Indra Saputra; Deastry Nabilah; Malini Dwi Rahma Dona; Sharfina Ningma Zatalini; Zenitha Zakiah; Elda Ulyanti (CV. Doki Course and Training, 2023)
This study aims to determine the picture and how the influence of social media on communication skills in adolescents and also improve communication skills and social skills of adolescents. This research will be conducted from April to May 2023. The method used in this study is quantitative correlational with a sample of 72 students at UIN Raden Fatah Palembang. Quantitative data analysis using google form. The results showed both positive and negative impacts of social media. Based on social media items, adolescents with vulnerable age (20-21 years) spend more time using social media than adolecents with vulnerable age (18-19 years), where there is a rasio that is not too significant at 44.95:46.25. while based on gender differencess between women and men, this cannot be used as one of the crucial factors in this context because sometimes the traits and habits between the two are relatively the same.